Performance and Emission Characteristics of Diesel Engines Using Biodiesel from Waste Cooking Oil with Cetane Number Improver - Suardi; Faisal Mahmuddin; Syerly Klara; Muhdar Tasrief; Muhammad Uswah Pawara; Hijriah; Muhammad Reza Fachrul Jaya (International Journal of Marine Engineering Innovation and Research, 2024)
The depletion of fossil fuel reserves has led to a global energy crisis, with increasing demand for alternative energy sources. Diesel fuel shortages, especially in countries like Indonesia, have driven the exploration of biodiesel as a sustainable alternative. This study aims to convert waste cooking oil (WCO) into biodiesel, with the addition of a cetane number improver (CNI) to enhance its performance in diesel engines. The biodiesel was produced through methanolysis, and 2-Ethylhexyl Nitrate (EHN) was added to improve combustion and reduce engine knocking. The results show that the produced biodiesel had a density of 856 Kg/m³ for B0, 872.7 Kg/m³ for B0 with CNI, and 872.1 Kg/m³ for B50CN. Viscosity values were 2.32 cSt for B0, 5.645 cSt for B50, and 4.722 cSt for B50CN. The cetane index was 49.2 for B50 and B50CN, while B0 had a value of 48. The emissions measured included CO levels of 194 mg/Nm³ for B0, 254 mg/Nm³ for B50, and 280 mg/Nm³ for B50CN. NOx emissions were 852 mg/Nm³ for B0, 755 mg/Nm³ for B50, and 825 mg/Nm³ for B50CN. Oxygen content was 15.9% for B0, 14.9% for B50, and 16.2% for B50CN. The findings indicate that adding EHN to WCO biodiesel improves fuel properties but increases emissions of CO and NOx. Overall, WCO-based biodiesel with EHN is a viable alternative fuel that balances performance improvements with environmental considerations.